Bright four-color quadripartite entanglement from quasi-phase-matching cascaded nonlinear optical frequency conversion. (23rd May 2019) - Wang, Junfeng; Liu, Bo; Liu, Shaopeng; Sun, TingTing; Zhao, Lilong; Mao, Yaya; Song, Zhenzhen; Wu, Yongfeng
Abstract: We propose an experimentally feasible scheme to produce bright four-color continuous-variable entanglement by intracavity quasi-phase-matching cascaded nonlinear optical frequency conversion in only one optical superlattice. The second, third and fourth harmonics can be generated by frequency doubling of the input fundamental field at frequency, the sum frequency of fundamental and second harmonic fields, and frequency doubling of the second harmonic field, respectively. The entanglement properties influenced by system parameters are theoretically discussed according to the sufficient inseparability criterion proposed by van Loock and Furusawa. Such compact multipartite continuous-variable entanglement has potential applications in quantum communication and computation networks.